Oxidative stress and inflammation combine to exacerbate cochlear damage and sensorineural hearing loss in C57BL/6 mice - Zhongwu Su; Yuyan Chen; Yu Liu; Jinyuan Cao; Jie Cui; Haitong Chen; Qi Li (Frontiers in Neuroscience)
BackgroundSensorineural hearing loss (SNHL) is among the most common sensory disorders, significantly affecting various aspects of the quality of life of an individual. Oxidative stress and inflammation have been involved in the progression of various forms of SNHL and are potential pathological mechanisms of the disorder. However, the synergistic effects of oxidative stress and inflammation on cochlear function is not completely understood.MethodsWe explored the effects of oxidative stress and inflammation on cochlear damage and hearing impairment in male C57BL/6 mice aged 6 to 7 weeks. These in the experimental group were administered with oxidant Menadione bisulfite (MD) and the endotoxin lipopolysaccharide (LPS) via intraperitoneal route to induce oxidative stress and inflammation, whereas the control group received saline. The degree of cochlear damage was analyzed based on auditory thresholds, hair cells (HCs) loss, and the expression of protein markers related to oxidative stress, inflammation, necroptosis, and ferroptosis.ResultsAfter six days of alternating MD and LPS injections, there was a notable elevation in hearing thresholds, which was associated with a substantial loss of HCs and spiral ganglion cells. Immunofluorescence analysis demonstrated the activation of oxidative stress, inflammation, necroptosis, and ferroptosis signaling pathways after treatment. Notably, the administration of either MD or LPS alone did not result in significant changes.ConclusionThese findings indicate that the interaction between oxidative stress and inflammation may exacerbate cochlear damage and contribute to hearing loss, potentially through the activation of necroptosis and ferroptosis pathways. Our results may identify potential therapeutic targets for the management of SNHL.